2009
DOI: 10.1073/pnas.0900238106
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of arsenic by a Yellowstone thermoacidophilic eukaryotic alga

Abstract: Arsenic is the most common toxic substance in the environment, ranking first on the Superfund list of hazardous substances. It is introduced primarily from geochemical sources and is acted on biologically, creating an arsenic biogeocycle. Geothermal environments are known for their elevated arsenic content and thus provide an excellent setting in which to study microbial redox transformations of arsenic. To date, most studies of microbial communities in geothermal environments have focused on Bacteria and Arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
234
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 264 publications
(246 citation statements)
references
References 33 publications
(37 reference statements)
6
234
1
Order By: Relevance
“…Arsenic is ubiquitous in aquatic environments where various kinds of cyanobacteria are distributed (Qin et al, 2006(Qin et al, , 2009Zhang et al, 2013), so cyanobacteria have evolved several ways to detoxify As in order to survive in the environment (Aurilio et al, 1994;Knauer et al, 1999). In this study, our results showed that S. platensis could grow at high concentrations of the toxic metalloid and had the capability of As(III) accumulation and biotransformation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Arsenic is ubiquitous in aquatic environments where various kinds of cyanobacteria are distributed (Qin et al, 2006(Qin et al, , 2009Zhang et al, 2013), so cyanobacteria have evolved several ways to detoxify As in order to survive in the environment (Aurilio et al, 1994;Knauer et al, 1999). In this study, our results showed that S. platensis could grow at high concentrations of the toxic metalloid and had the capability of As(III) accumulation and biotransformation.…”
Section: Discussionmentioning
confidence: 60%
“…The huge difference between the sequences may explain the difference in methylation products. In addition, As(III) was seen to be transformed to DMA(V) within 30 min, and the catalytic rate of SpArsM was much faster than that of other ArsMs (Qin et al, 2009;Wang et al, 2014a;Zhang et al, 2015). Meanwhile, the intermediate MMA(III) and MMA(V) were absent in the in vitro enzyme activity assays when the reaction was performed at optimal conditions, and only MMA(V) was observed when the enzyme was impaired, for example under higher or lower temperature.…”
Section: Discussionmentioning
confidence: 99%
“…PCC 7120 incorporate As into sugars as Oxo-Gly and Oxo-PO 4 . This is the first report clearly demonstrating that cyanobacteria have an ability to produce arsenosugars, which could well have important implications for freshwater lakes and hot springs occurring in the vicinity of soils rich in As (there is in fact a report of arsenosugars in hotspring mats [38] ).…”
Section: Discussionmentioning
confidence: 77%
“…These biotransformations include redox cycles between the relatively innocuous pentavalent arsenate and the considerably more toxic and carcinogenic trivalent arsenite (2,3). In addition, many microbes, both prokaryotic and eukaryotic, have arsM genes for inorganic arsenite [As(III)] S-adenosylmethionine methyltransferases that methylate inorganic As(III) to mono-, di-, and tri-methylated species (4,5). The genes encoding arsenic transforming enzymes are widely distributed, and these arsenic biotransformations have been proposed to play significant roles in the arsenic biogeocycle and in remodeling the terrain in volcanic areas such as Yellowstone National Park and regions of the world with high amounts of arsenic in soil and water such as West Bengal and Bangladesh (3,6).…”
mentioning
confidence: 99%